Knowledge, Attitudes and Practices regarding Lung Cancer and Lung Cancer Screening in Greece: A Cross-sectional Study - Kourlaba, Georgia; Triantafyllou, Christos; Lampropoulou, Dimitra Ioanna; Faropoulou, Ifigenia; Gounelas, George; Gamvrouli, Maria; Zyga, Sofia; Rikos, Nikos; Myrianthefs, Pavlos (Archives of Clinical and Biomedical Research, 2024)
This study aimed to investigate the knowledge, attitudes and practices of Greek general population regarding lung cancer (LC) and LC screening and the factors that may influence these aspects. A nationwide crosssectional survey was conducted. The total mean (SD) knowledge score was 4 1 (17) over a maximum score of 8 68 1% of participants correctly mentioned low-dose computed tomography (LDCT) as screening method for LC and 87 7% believed that LC screening should be a priority for the state and should be provided for free to all citizens (91 1%) 80 0% mentioned that they would be willing to undergo LDCT screening if recommended by their physician, or if they received a state-issued text message. Higher total knowledge scores were significantly associated with greater probability of willingness to undergo LDCT. These findings underline the need to implement public health interventions towards increasing community awareness regarding benefits of screening and early diagnosis of LC.